2009
DOI: 10.1111/j.1758-2229.2009.00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographical patterns of soil bacterial communities

Abstract: This study provides the first maps of variations in bacterial community structure on a broad scale based on genotyping of DNA extracts from 593 soils from four different regions of France (North, Brittany, South-East and Landes). Soils were obtained from the soil library of RMQS ('Réseau de Mesures de la Qualité des Sols' = French soil quality monitoring network). The relevance of a biogeographic approach for studying bacterial communities was demonstrated by the great variability in community structure and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
50
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 15 publications
12
50
0
2
Order By: Relevance
“…The size and shape of the neighbourhood was in agreement with previous spatial analyses of habitat and genetic data that demonstrated significant spatial structures 27 when the radius was at least 140 km ( Table 2). As all the parameters are estimated with errors, the relationships were best modelled by a type II linear regression model (ordinary least squares method).…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…The size and shape of the neighbourhood was in agreement with previous spatial analyses of habitat and genetic data that demonstrated significant spatial structures 27 when the radius was at least 140 km ( Table 2). As all the parameters are estimated with errors, the relationships were best modelled by a type II linear regression model (ordinary least squares method).…”
Section: Methodssupporting
confidence: 90%
“…Recent microbial biogeography studies have revealed that the main environmental filters shaping spatial microbial diversity distribution are soil physico-chemical characteristics, land use and plant cover, whereas climatic and geomorphologic filters are less important 9,11,15,37 . Similar filters were also reported to explain soil bacterial community distribution in contrasted ecological regions at the scale of France 27,34 .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…To increase our understanding of the mechanisms driving the distribution of microorganisms and the processes shaping these communities, characterization of their spatial patterns at various scales has become of great interest. Spatial analysis of microbial diversity have revealed a significant effect of distance on the taxa distribution of soil microorganisms ranging from a few centimeters to meters and even kilometer at the landscape scale (Franklin and Mills, 2003;Ritz et al, 2004;Dequiedt et al, 2009;Philippot et al, 2009a). However, Green et al (2008) recently underlined the importance of focusing on trait-based rather than taxonomic biogeography in microbial ecology similar to what has been done for example in plant ecology (Enquist et al, 2007;Savage et al, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…pH, the amount of soil contaminants or salts) and the physical properties of soils such as porosity and bulk density, both of which are affected by compaction or sealing. However in the last years, several studies on soil biodiversity have been started, allowing a better comprehension of the biogeography of soil organisms (Dequiedt et al, 2009;Cluzeau et al, 2009;Griffiths et al, 2011). Other recent research has targeted the investigation of the relationships between soil parameters, land management practices and soil biodiversity patterns (Gardi et al, 2008;Bru et al, 2011;Dequiedt et al, 2011;Keith et al, 2011), while other investigations are more focused on the contribution of soil biota to the provision of ecosystem services (Mulder et al, 2011).…”
Section: Tartes) 4th Row -Fruiting Bodies Of a Myxomycete (Slime Moumentioning
confidence: 99%